Clojure Data Structures and Algorithms Cookbook - Naccache, Rafik; Naccache, Rafik (Packt Publishing, 2015)
25 recipes to deeply understand and implement advanced algorithms in ClojureAbout This BookExplore various advanced algorithms and learn how they are used to address many real-world computing challengesConstruct elegant solutions using impressive techniques including zippers, parsing, and pattern matchingSolve complex problems by adopting innovative approaches such as logic or asynchronous programmingIn DetailData-structures and algorithms often cross your path when you compress files, compile programs, access databases, or simply use your favourite text editor. Understanding and implementing them can be daunting. Curious learners and industrial developers can find these complex, especially if they focus on the detailed implementation of these data structures.Clojure is a highly pragmatic and expressive language with efficient and easy data manipulation capabilities. As such, it is great for implementing these algorithms. By abstracting away a great share of the unnecessary complexity resulting from implementation, Clojure and its contrib libraries will help you address various algorithmic challenges, making your data exploration both profitable and enjoyable.Through 25 recipes, you'll explore advanced algorithms and data-structures, well served by a sound Clojure implementation.This book opens with an exploration of alternative uses of the array data-structure, covering LZ77 compression, drawing fractals using Pascal's triangles, simulating a multi-threaded program execution, and implementing a call-stack winding and un-winding operations.The book elaborates on linked lists, showing you how to construct doubly linked ones, speed up search times over the elements of such structures, use a linked-list as the foundation of a shift-reduce parser, and implement an immutable linked-list using skew binary numbers representation.After that, the tree data-structure is explored, focusing on building self-balancing Splay Trees, designing a B-Tree backing-up an efficient key-value data-store, constructing an undo capable Rope, and showing how Tries can make for an auto-completing facility.Next, some optimization and machine learning techniques are discussed, namely for building a co-occurrence-based recommendation engine, using branch-and-bound to optimize integral cost and profit problems, using Dijkstra's algorithm to determine optimal paths and summarizing texts using the LexRank algorithm.Particular attention is given to logic programming, you will learn to use this to discover interesting relations between social website data, by designing a simple type inferencer for a mini Java-like language, and by building a simple checkers game engine.Asynchronous programming will be addressed and you will design a concurrent web-crawler, an interactive HTML5 game, and an online taxi booking platform.Finally, you'll explore advanced cases for higher order functions in Clojure while implementing a recursive descent parser using efficient mutual resucrsion, devising a mini resusable firewall simulator thanks to Clojure 1.7 new tansducers feature or building a simple unification engine with the help of Continuation Passing Style.What You Will LearnExplore alternative uses of classical data-structures like arrays and linked-listsDiscover advanced types of tree data-structuresExplore advanced machine learning and optimization techniquesUtilise powerful Clojure libraries, such as Instaparse for parsing, core.match for pattern matching, clojure.zip for zippers, and clojure.matrix for matrix operationsLearn logic programming through the usage of the library core.logicMaster asynchronous programming using the core.async librarySee the transducers in action while resolving real-world use-casesWho This Book Is ForIf you are an experienced Clojure developer, longing to take your knowledge to the next level by discovering and using advanced algorithms and seeing how they can be applied to real-world problems, then this book is for you.Style and approachThis book consists of a set of step-by-step recipes, each demonstrating the material covered in action so it is put in context. When necessary, pointers to further resources are provided.